Translation and psychometric evaluation of the Diabetes Education Questionnaire (DATE-Q) from English to Marathi – assessing reliability, validity, and cross-cultural equivalence - Kulkarni, Sharvari J.; Lima de Melo Ghisi, Gabriela; Jaiswal, Varoon C.; Pawar, Pournima; Kharatmal, Deepali R.; Kangude, Mithali M. (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The DiAbeTes Education Questionnaire (DATE-Q) is a self-administered tool created to evaluate disease-related knowledge and knowledge of five core components of rehabilitation: exercise, diet, psychological well-being, self-management and complications. The aim was to translate and adapt the DATE-Q into Marathi language and to evaluate the validity and reliability among diabetes and prediabetic patients. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Material and methods. The study was carried out following standard stepwise Beaton and COSMIN guidelines to complete the translation and psychometric validation of the questionnaire. The pre-final version was evaluated in 30 individuals with diabetes or prediabetes. Test-retest reliability and internal consistency were assessed among 200 individuals with type 2 diabetes using Cronbach’s alpha and intraclass correlation coefficients respectively. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Results. The original and translated versions did not conceptually differ from each other. DATE-Q has ten elements that were culturally adjusted. Based on suggestions from the expert group and the results of the pilot tests, cross-cultural modifications were made. The value of 0.935 for Cronbach’s alpha shows a very high level of internal consistency. For single and average measures, the intraclass correlation coefficient is 0.985 and 0.993 resp. which indicates an excellent level of reliability. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Conclusion. The DiAbeTes Education Questionnaire is a reliable and valid tool for evaluating knowledge among Marathi-speaking patients.